PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI METODE PEMBELAJARAN CONTEXSTUAL AND LEARNING - Rachmadtullah, Reza; Wardani, Prayuningtyas Angger (JURNAL PENDIDIKAN DASAR, 2016)
Abstrack : The purpose of this study was to determine how the application of methods Contextual Learning And, to improve learning outcomes Civic Education about my hero. Research conducted at the Elementary School District 22 Mempawah Mempawah West Kalimantan, with research subjects fifth grade students totaling 30 people. This research is an action using a model Kemmis and McTaggart, conducted in two cycles. Each cycle consists of planning, implementing action, observation, and reflection action. The data collection process through tests mastery of learning outcomes Civics students, especially the material to understand the meaning and relevance of the symbols of the precepts of Pancasila in the understanding of Pancasila as a whole, and nontes be the observation of the implementation of the method of learning through methods Contexstual And Learning by using observation sheet activities of teachers and students, interviews, field notes, and documentation of results. The results showed an increase learning outcomes Citizenship Education about understanding the meaning and relevance of symbols in understanding the precepts of Pancasila Pancasila as a whole. This is evidenced by the value of learning outcomes Citizenship Education students about the hero in the first cycle is 50% of students who completed an average of 69 classes, were increased in the second cycle reaches 80% of students who completed, with an average grade 77. Activities of teachers and students according to the steps of this method reach 100% at the end of the second cycle.Keywords: Learning Outcomes, Contexstual Method And Learning, Civic EducationAbstrack : Tujuan penelitian ini adalah untuk mengetahui cara penerapan metode Contexstual And Learning, untuk meningkatkan hasil belajar Pendidikan Kewarganegaraan tentang pahlawanku. Penelitian dilaksanakan di Sekolah Dasar 22 Mempawah Kabupaten Mempawah Kalimantan Barat, dengan subjek penelitian siswa kelas V yang berjumlah 30 orang. Penelitian ini merupakan penelitian tindakan dengan menggunakan model Kemmis dan McTaggart, dilakukan dalam dua siklus. Setiap siklus terdiri dari tahap perencanaan, implementasi tindakan, pengamatan, dan refleksi tindakan. Proses pengumpulan data melalui tes penguasaan hasil belajar Pendidikan Kewarganegaraan siswa khususnya materi memahami makna dan keterkaitan simbol-simbol sila pancasila dalam memahami pancasila secara utuh, dan nontes berupa hasil observasi pelaksanaan metode pembelajaran melalui metode Contexstual And Learning dengan menggunakan lembar pengamatan aktivitas guru dan siswa, wawancara, catatan lapangan, dan hasil dokumentasi. Hasil penelitian menunjukkan adanya peningkatan hasil belajar Pendidikan Kewarganegaraan tentang memahami makna dan keterkaitan simbol-simbol sila pancasila dalam memahami pancasila secara utuh. Hal ini dibuktikan dengan nilai hasil belajar Pendidikan Kewarganegaraan siswa tentang pahlawanku pada siklus I yaitu 50% siswa yang tuntas dengan rata-rata kelas 69, meningkat pada siklus II mencapai 80% siswa yang tuntas, dengan rata-rata kelas 77. Aktivitas guru dan siswa sesuai langkah-langkah metode ini mencapai 100% pada akhir siklus II.Kata kunci: Hasil Belajar, Metode Contexstual And Learning, Pendidikan Kewarganegaraan